Interruptions experienced by nurses during pediatric medication administration in China: An observational study. Issue 4 (23rd July 2019) - Zhao, Junwen; Zhang, Xiaoling; Lan, Qiaoling; Wang, Wuni; Cai, Yinsha; Xie, Xiaohua; Xie, Jianfei; Zeng, Yingchun
Abstract: Purpose: The objectives of this study were to describe (a) the frequency of interruptions experienced by a pediatric nurse per hour, (b) the sources of interruptions experienced by a pediatric nurse, and (c) the interruption outcomes during pediatric medication administration. Design and Methods: This design of this study was a cross‐sectional observational study. A convenience sample of pediatric nurses was used in this study. The interruption observation sheet was used to collect data about the frequency, sources, and outcomes of interruptions. Results: There was a total of 43 nurses were observed in more than 180 medication administration rounds. An interruption rate of 94.51% occurred during pediatric medication administration. The frequency of interruptions was three or more times (51.04%). The most common source of interruption was attributed to the working environment (32.37%). The second most frequent reason for interruption came from personnel, such as caregivers (24.48%), followed by physicians (10.79%), and other nursing staff (9.54%). The third most common source of interruption was communication issues, including patient interviews, patient reports, and case discussion (8.71%). Six errors (2.49%) were reported out of 241 interruptions as a result of interruptions. In specific, causes of errors during pediatric medication administration were due to wrong medication dose. Practice Implications: This study provides important information on interruptions experienced by pediatric nurses during medication administration in Chinese hospital settings and found that interruptions frequently occur in pediatric units.